The first outbreak of feline panleukopenia virus infection in captive Pallas’s cats in Xining Wildlife Park - Wei, Jingjie; Shi, Yuqi; Wang, Xiaofei; He, Shunfu; Qi, Xinzhang; Lu, Rong; Gao, Yuhang; Liu, ZiChen; Wang, Yingyun; Wu, Yuanheng; Jin, Yipeng (Frontiers in Veterinary Science, 2024)
IntroductionIn August 2021, an outbreak of Feline Panleukopenia Virus (FPV) was observed in four 3-month-old Pallas’ cats at Xining Wildlife Park. Despite timely intervention, the Pallas’cat cubs continued to experience clinical symptoms including diarrhea, seizures, and decreased white blood cell count, and all four cats died.MethodsFPV clinical suspicions were initially confirmed by positive Polymerase Chain Reaction (PCR) testing. Pathological and immunohistochemical examinations (IHC) were performed on some organs, and the results showed that, encephalitis, viral enteritis, and splenitis occurred.ResultsThe virus replicates extensively in the cytoplasm of lymphocytes and macrophages in the lamina propria of the small intestine mucosa. A strain of FPV was successfully isolated and culture in CRFK cells. Through molecular identification, sequence analysis, and phylogenetic analysis of the VP2 gene in this strain, we have revealed the presence of a novel synonymous mutation. From July to December 2021, surveillance on stray cats and susceptible wildlife at Xining Wildlife Park indicated widespread FPV transmission.DiscussionThe findings highlight the urgent need for ongoing epidemiological monitoring and active disinfection measures to prevent FPV transmission in wildlife parks.